EFFECT OF SPERM INSEMINATION DURATION ON IN VITRO FERTILISATION (IVF) PERFORMANCE IN GOATS - W.L., Tan; W.E., Wan Khadijah; R.B, Abdullah (Malaysian Journal of Science, 2011)
The objective of this study was to evaluate the effect of sperm insemination duration during in vitro fertilisation (IVF) on the cleavage rate of goat embryos. Goat oocytes were retrieved through the slicing of ovaries obtained from abattoir and laparoscopic oocyte pick-up (LOPU). For in vitro maturation (IVM), the collected cumulus oocyte complexes (COCs) were matured and then incubated overnight in CO2 (5%) incubator at 38.5Â°C for 24-27 hr (abattoir source) or 18-21 hr (LOPU source). Oocytes were partially denuded and co-incubated with post-thawed sperm with concentration of 1x106 sperm/ml. After 8-14 hr or 18- 24 hr of insemination, in vitro culture (IVC) of presumptive zygotes were further incubated in CO2 (5%) incubator at 38.5Â°C for preimplantation embryonic development. The cleavage of the embryos was observed and recorded daily under inverted microscope. The fertilisation rate with insemination duration of 8-14 hr (39.82%) was higher than that with 18-24 hr (33.59%); however, there was no significant difference (P>0.05) between 2 groups of insemination durations. There was significant (P<0.05) decrease as the embryo developmental stages increased. Generally, the embryo developmental rates of all stages for insemination durations of 8-14 hr were higher than that of 18-24 hr, which were 49.36 vs. 27.92%; 33.77 vs. 22.29%; 7.32 vs. 2.08% and 0.56 vs. 0.00% for 2-, 4-, 8-cell and morula, respectively. In conclusion, shorter insemination duration may be needed to improve the IVF performance in goats.